Control Design For Shunt Active Power Filter Based On p-q Theory In Photovoltaic Grid-Connected System - Moh. Jauhari; Dedet Candra Riawan; Mochamad Ashari (Institute of Advanced Engineering and Science, 2018)
This paper presents the control for Shunt Active Power (SAPF) filter in photovoltaic (PV) systems connected to the grid. The proposed configuration of the system consists of a photovoltaic array that connected to the grid through the three-phase inverter topology that also serves as an active filter. Photovoltaic is coupled in parallel with the direct curret (DC) side of the active filter. With this configuration, can be obtained three advantages, namely the elimination of harmonic currents caused by nonlinear load, reactive power injection, and injection of active power generated photovoltaic. The p-q Theory is used to calculate the harmonic reference current to be used to control the active filter coupled fotovoltaic in generating anti-harmonic currents. The results show that system can reduce harmonic distortion from THD 27.22% to be THD 1.05%, whereas when the active power from photovoltaic injected, the THD become 2.01%. Power sharing can also be seen from this study.